2010
DOI: 10.1002/hed.21652
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of facial paralysis caused by ethanol sclerotherapy for facial venous malformation

Abstract: The zygomatic and temporal branches of the facial nerve were the most vulnerable to injury after ethanol sclerotherapy. Surgeons are thus called on to pay more attention when performing ethanol sclerotherapy in those areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Of those who were hydrated after hemoglobinuria, no patient suffered from renal impairment. Although 3 cases of facial paralyzes after ethanol sclerotherapy occurred in our sample (all 3 were transient), it is important to highlight the need for caution when performing ethanol instillation in the zygomatic, temporal, buccal, and parotid areas …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Of those who were hydrated after hemoglobinuria, no patient suffered from renal impairment. Although 3 cases of facial paralyzes after ethanol sclerotherapy occurred in our sample (all 3 were transient), it is important to highlight the need for caution when performing ethanol instillation in the zygomatic, temporal, buccal, and parotid areas …”
Section: Discussionmentioning
confidence: 87%
“…Although 3 cases of facial paralyzes after ethanol sclerotherapy occurred in our sample (all 3 were transient), it is important to highlight the need for caution when performing ethanol instillation in the zygomatic, temporal, buccal, and parotid areas. 24 This study had several limitations. First, we did not include a large number of patients and these were part of a retrospective data analysis.…”
Section: Discussionmentioning
confidence: 93%
“…10 Articles cited in the Introduction herein have generally reported that the risk of facial nerve injury is 5% to 10% for treatment of vascular anomaly in the cervicofacial region. [1][2][3][4] The reason for dramatically improved facial nerve outcomes is in part explained by the FNM but also because the FNM enables (1) improved planning for an approach that has potentially less collateral tissue damage and (2) focused concentration by the surgeon, with confidence in the intraoperative interrogations of the nerve, as reported by the neurophysiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Vigilant planning and injection are recommended to reduce this risk, with particular attention with VM in the head and neck. 57 Glue boluses remain inert for most patients, but may rarely become infected and require antibiotics. Allergy to nBCA is rare, but may produce severe pruritus.…”
Section: Procedure-related Complicationsmentioning
confidence: 99%